Effects of varying protein sources and ammonium chloride sources on Boer goat growth performance and carcass traits - Markland, Mary L.; Sorensen, Rachel J.; Crane, Alison R.; Lattimer, James M.; Jones, Cassandra K. (My University, 2018)
Although the global goat population has increased 34% in the past 10 years, there is very limited research on goat nutrition. Soybean meal (SBM) is the traditional protein source used in goat diets, but there has been growing interest in using other protein sources to promote growth. The purpose of this study was to evaluate the effect of varying protein sources, such as SBM, dried distillers grains with solubles (DDGS), and SoyPlus (Dairy Nutrition Plus), combined with ammonium chloride (AmCl) sources, such as AmCl and SoyChlor (Dairy Nutrition Plus) on growth performance and carcass traits. Seventy-five Boer goats were group housed and randomly allocated to 1 of 5 treatments (15 goats per treatment; 3 goats per pen); 1) SBM plus AmCl, 2) DDGS plus AmCl, 3) SoyPlus plus AmCl, 4) SBM plus SoyChlor, 5) SoyPlus plus SoyChlor. The GLIMMIX procedure of SAS was used to analyze data. With P<0.05 denoting significant differences, there was no difference in body weight (P>0.05), average daily gain (ADG) (P=0.0869), average daily feed intake (ADFI) (P=0.1412), and gain to feed ratio (G:F) (P=0.3739). However, based on feed costs, goats fed DDGS had lower feed cost per goat (P=.001) than goats fed SBM. Feeding treatment 2 (DDGS plus AmCl) gave the most savings in diet cost. Regarding carcass traits, SBM resulted in a greater loin eye area (LEA) than DDGS (P=0.04) and SoyPlus (P=0.005), while AmCl source had no effect on LEA (P=0.750). There was no significant difference in carcass yield (P=0.52) and backfat depth (P=0.71). Results indicate that farmers could utilize DDGS plus AmCl for high growth performance at a lower cost.
Keywords: Fall 2018